Geotechnical properties of natural composite rock in Ibadan, Nigeria (2012)
The physical property of a rock is a pointer to its suitability for civil engineering works. In this study the suitability of composite rock as construction materials is established. Thirty-four fresh block samples of quartz-schist masses were obtained from three locations in Ibadan, Nigeria. Thin sections were prepared from two representative samples, while others were subjected to standard geotechnical laboratory testing. Regression plots were made to assess the degree of association between pairs of dependent physical parameters of the rock. The results show in thin section that individual quartz crystals of the samples have complexly sutured outlines and mutual interlocking. Modal analysis reveals quartz as the dominant mineral with subordinate amounts of muscovite. The density (y) is the least variable parameter and ranges between 2600 and 2660 kg/m3. Water absorption ranges between 0.64 and 3.39 %, indicating good rock materials for construction. Regression analysis shows that approximately 20% of the variation in density and 2% of the void ratio were associated with porosity and water absorption capacity of the rock respectively. These are due to different proportions of quartz and muscovite with voids in the quartz-schist.